Pre- and post-move exposure to air pollution and neighborhood socioeconomic status - Liu, Chelsea; Bennett, Erin E.; Lynch, Katie M.; Xu, Xiaohui; Park, Eun Sug; Ying, Qi; Smith, Richard L.; Stewart, James D.; Whitsel, Eric A.; Kaufman, Joel D.; Stapp, Emma K.; Power, Melinda C. (The Science of the total environment, 2025)
Nearly 10 % of the U.S. population moves in a given year. We aimed to examine differences in neighborhood socioeconomic status (nSES) and ambient air pollution concentrations before and after a residential move, whether change varies by distance of the move, and whether moving is a potential source of bias in estimating relationships between contextual exposures and outcomes. We used data from participants in the Atherosclerosis Risk in Communities (ARIC) Study with geocoded addresses at Visit 2 (Visit 2; 1990–1992) and Visit 3 (Visit 3; 1993–1995). We quantified nSES using the 1990 census and estimated concentrations of fine particulate matter (PM2.5), ozone (O3) and nitrogen dioxide (NO2). We defined short-distance and long-distance movers as having moved less and more than the median move distance of 4.3 miles, respectively. We quantified Visits 2 to 3 change in nSES and air pollution for short and long-distance movers, examined change in air pollution after accounting for temporal trends, and conducted a quantitative bias analysis to estimate the bias introduced by not accounting for moving in example studies of PM2.5 and health. On average, compared to non-movers, short-distance movers relocated to neighborhoods with better nSES and similar air pollution concentrations, while long-distance movers relocated to neighborhoods with worse nSES but lower exposure to air pollution. The quantitative bias analysis suggested there was little to no bias in the PM2.5-health relationship from not accounting for relocation, likely due to relatively little overall difference in PM2.5 exposures observed with relocation. Change in nSES and air pollution with a residential move differs by move distance. However, not accounting for relocation may not lead to significant bias in the relationship with the health outcome. Understanding the extent to which contextual exposures change after a move can clarify whether accounting for bias due to relocation is necessary. [Display omitted] •Moving changes exposure to neighborhood SES (nSES) and air pollution•Short-distance moves led to better nSES, with little change in pollution levels.•Long-distance moves led to worse nSES but lower air pollution exposures.•PM2.5-health relationship showed minimal bias from not accounting for moving.